Karakteristik Ruang Kampung Melayu di Pontianak: Studi Kawasan Pemukiman di Kelurahan Bangka Belitung Laut - Zain, Zairin; Bagaskara, Jefri (Nature : National Academic Journal of Architecture, 2024)
The use of spatial organization in Malay villages, especially the Bangka Belitung village settlements in Pontianak city, indirectly creates space in areas that are used as settlements. The background to the formation of the Bangka Belitung village is a form of moving from a place, recognizing that the area belongs to it, followed by daily activities and other people's views on the area. People choose a place to live according to their living needs, such as the people of Bangka Belitung village who choose to live on the banks of the Kapuas river to take advantage of the various functions of the river which is often used as a characteristic of the Malay nation. The togetherness of people who socialize in one place makes spaces a place to support their needs. This is what forms the character of a residential area. This research aims to determine the character of the space formed in Bangka Belitung village, Pontianak city. Any data obtained uses literature methods and information mining on the internet. Apart from that, observing the area to take pictures is a necessity in analyzing the character of the area's residential space. Then it is processed using qualitative descriptive methods to describe, explain and answer the problems of a research. From the research results, it was found that Bangka Belitung Village has good territory/boundaries administratively and in terms of character interactions, diverse spatial forms, and is oriented towards roads and rivers.